Notizie di frammenti liturgico-agiografici contenuti nell’Archivio Comunale di Gemona del Friuli (UD) - Guariglia, Federico (Vox Patrum, 2023)
The contribution examines the membra disiecta of the Municipal Archive of Gemona del Friuli (UD). In order to comply with the topic of the conference, three parchment fragments (1654.26; 1654.32; 1654.33) from the religious field have been analyzed. These are three texts used for the Mass, which combine sung parts with hagiographic texts, such as the Life of Saint Cecilia, and Biblical texts (e.g. the Gospel of Luke). A description and edition of the text is provided for each fragment. The study of the three unpublished codices makes it possible to continue the discussion on the Friulian Middle Ages, which is often lacunar, and to reconstruct the religious and cultural life in the community of Gemona del Friuli.